2006
DOI: 10.1139/w06-078
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli inactivation mechanism by pressurized CO2

Abstract: The effects of pressurized CO2 on the survival of Escherichia coli and the mechanism of cell inactivation were studied. Bacterial cultures were inoculated in nutrient broth and incubated at 30 degrees C for 18 h. Exposure of the cells to CO2 under pressures ranging from 2.5 to 25 MPa and at temperatures between 8 and 40 degrees C was performed in a double-walled reactor with a 1 L capacity. The effect of the treatment on the cells was evaluated by plating and by transmission and scanning electron microscopy ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…The inoculated media was immediately placed in a 4 L pressure vessel (Alloy Products Corp, Waukesha, WI) and made anaerobic through the use of a GasPak ™ EZ Anaerobe Container System Sachet (BD, Franklin Lakes, NJ).The serum bottles in the vessels were then pressurized to 1.0 MPa in the field with ultrapure CO 2 . Previous work has shown that CO 2 is very effective sterilant (Nakamura et al, 1994;Isenschmid et al, 1995;Ballestra et al, 1996;Shimoda et al, 1998;Hong and Pyun, 1999;Erkmen, 2000;Spilimbergo and Bertucco, 2003;Watanabe et al, 2003;Damar and Balaban, 2006;Oule et al, 2006Oule et al, , 2010Song et al, 2007). With this in mind, we reasoned that cultures grown at very high CO 2 pressures would likely result in a sterilization of most viable microorganisms, especially those accidentally introduced through contamination.…”
Section: Field Samplingmentioning
confidence: 91%
“…The inoculated media was immediately placed in a 4 L pressure vessel (Alloy Products Corp, Waukesha, WI) and made anaerobic through the use of a GasPak ™ EZ Anaerobe Container System Sachet (BD, Franklin Lakes, NJ).The serum bottles in the vessels were then pressurized to 1.0 MPa in the field with ultrapure CO 2 . Previous work has shown that CO 2 is very effective sterilant (Nakamura et al, 1994;Isenschmid et al, 1995;Ballestra et al, 1996;Shimoda et al, 1998;Hong and Pyun, 1999;Erkmen, 2000;Spilimbergo and Bertucco, 2003;Watanabe et al, 2003;Damar and Balaban, 2006;Oule et al, 2006Oule et al, , 2010Song et al, 2007). With this in mind, we reasoned that cultures grown at very high CO 2 pressures would likely result in a sterilization of most viable microorganisms, especially those accidentally introduced through contamination.…”
Section: Field Samplingmentioning
confidence: 91%
“…Carbonation at 7-21 MPa and 35℃ for 15 and 20 min also induces damage to the biofunction of proteins or the balance of enzymatic activities (Lin et al, 1993). In addition, both heat treatment and carbonation cause structural changes in microbial cells (Tsuchido et al, 1985;Oulé et al, 2006). We expected that combination of these treatments at milder conditions would induce damage to microbial cells severe enough to cause loss in viability, resulting in their effective inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Acidification of the cytoplasm has been proven to induce injury and loss of viability in microbial cells (Kim et al, 2008;Wu et al, 2007). Most studies on carbonation treatment for the inactivation of vegetative microorganisms have employed pressures ranging from 1−30 MPa with temperatures below 40℃ (Oulé et al, 2006;Garcia-Gonzalez et al, 2009;Shimoda et al, 2002). Oulé et al (2006) demonstrated that carbonation at pressures below 2.5 MPa and temperatures below 40℃ showed no inactivation effect on Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But their envelope deformed and wrinkled apparently compared to the untreated cells. Probably the cellular lipid extraction, a characteristic of SCCO 2 , led to the collapse of cell wall, so that the cellular shape changed after the treatment [11]. Likewise, some obvious changes of the SCCO 2 -treated cells were observed by TEM compared with the untreated cells.…”
Section: Observation Of Cell Structure Using Electron Microscopymentioning
confidence: 96%